A closed loop supply chain under retail price and product quality dependent demand. (October 2015) - Maiti, T.; Giri, B.C.
Abstract : Highlights: We study a hybrid manufacturing and remanufacturing process in a CLSC framework. In this study, the market demand is varying with retail price as well as the product's quality. We construct four different decentralized policies – manufacturer-led, retailer-led, third party-led and decentralized or Nash game along with centralized policy. A comparative study has been made for five different policies through numerical and sensitivity analysis. Abstract: The importance of remanufacturing of used products, maintaining the same quality as new ones has been widely recognized in practice. In this paper, we address a closed loop supply chain where the manufacturer manufactures a product with a decent quality acceptable to customers, and sells it through a retailer in the market. A third party collects the used products from consumers and sends to the manufacturer. The manufacturer re-manufactures the used product and the quality of remanufactured product is the same as that of the manufactured one. For such a closed loop supply chain, we construct five different scenarios – centralized, decentralized or Nash game and three different Stackelberg games, led by the manufacturer, retailer and third party respectively. We compare the optimal results to find out the best decentralized scenario out of the four mentioned. A numerical example is taken to study the impacts of product quality on demand as well as optimal decisions and investigate sensitivity of some key model-parameters.